COMPARATIVE EVALUATION OF THE AGRONOMIC PERFORMANCE OF TWO VARIETIES OF GROUNDNUTS (Arachis hypogaea L) CULTIVATED IN BENUE STATE, NIGERIA - Bitto, K.D.; Akinboye, O.E.; Shobo, A.B. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Groundnut (Arachis hypogaea L) is a species of the legume or family (Fabaceae). It is a tropical plant with high protein, oil, fatty acid, carbohydrates, vitamins and mineral contents. Due to the need to evaluate and compare the agronomic performance of the two Dominant Groundnut varieties in Benue State, Nigeria to identify the most suitable variety for cultivation in this region; a Comparative Evaluation of the Agronomic Performance of Samnut 23 and Samnut 24 cultivated on ridges made 0.5m apart in two Local Government Areas of Benue State was done after harvesting at maturity. Data was analysed statistically using the student t-test and Analysis of Variance (ANOVA). Canopy height, the number of single pods, the number of triple pods, the weight of single seeds, and the weight of triple seeds differed significantly (P<0.05) between Samnut 23A and Samnut 24A in Makurdi Area. The number of triple pods, the weight of single seeds, the weight of double seeds, the weight of triple seeds, the total weight of seeds and the weight of Haulms in Guma Area differed significantly (P<0.05) between Samnut 23B and Samnut 24B. They were significant differences in Canopy Height, Canopy Diameter, the no of single pods, No of triple pods, the weight of single seeds, the weight of double seeds , the weight of triple seeds, the total weight of seeds and the weight of Haulms (P<0.05) based on location.